Does pulmonary hypertension affect early-term outcomes of off-pump coronary artery bypass surgery? - Velioglu,Yusuf (2022)
SUMMARY OBJECTIVE: This study aimed to investigate the effect of preoperative pulmonary hypertension (PHT) on postoperative early mortality and morbidity in patients undergoing off-pump coronary artery bypass grafting (CABG). METHODS: A total of 1107 patients undergoing elective first-time off-pump CABG between January 2011 and April 2022 were included in this retrospective observational cohort study. The patients were categorized into two groups according to their preoperative systolic pulmonary artery pressure (SPAP) values. The PHT group (n=104) consisted of patients with a SPAP value >30 mmHg, while the non-PHT group (n=1003) consisted of patients with a SPAP value ≤30 mmHg. Patients’ preoperative demographics and clinical features, operative data, and postoperative outcomes were recorded and then compared between the groups. RESULTS: In the PHT group, the median age was significantly higher (66 vs. 63 years, p=0.001) and the median left ventricular ejection fraction level was significantly lower (45 vs. 50%, p=0.045) as compared to the non-PHT group. Additionally, the PHT group included a significantly greater percentage of patients with chronic obstructive pulmonary disease (22.1 vs. 7.4%, p=0.019). As perioperative early-term outcomes, complications, and mortality were considered, the groups were statistically similar, and there were no significant differences between the groups, except for the development of atrial fibrillation. CONCLUSION: For the first time in the literature, this study revealed that mild PHT (mean SPAP=38.9±8.7 mmHg) did not significantly affect early-term outcomes of off-pump CABG.